A new aerophilic species of the genus Diploneis (Bacillariophyta) from the Mawsmai cave of Meghalaya, Northeast India - Bhatt, Chintan; Karthick, Balasubramanian (Phytotaxa, 2020)
A new aerophilic species, Diploneis mawsmaii sp. nov., is here described from a speleo-environment. The species is found on mosses growing under the water dripping region of Mawsmai cave, Meghalaya state of India. It is discussed based on detailed light and scanning electron microscopic observations and compared with morphologically similar Diploneis species like D. modica Hustedt, D. modicahassiaca Lange-Bertalot & A. Fuhrmann, D. boldtiana Cleve and D. zula Kulikovskiy & Lange Bertalot. Diploneis mawsmaii possesses distinct morphological features such as a largely expanded central area bearing a prominent circular to oval central nodule and the internal structure exhibiting short striation with acute ends and the flattening of longitudinal canals at the central area. This discovery increases our understanding of cavern biodiversity in the Indo-Burma hotspot region.